Circulating Epstein-Barr virus in children living in malaria-endemic areas - Rasti, N.; Falk, K.I.; Donati, D.; Gyan, B.A.; Goka, B.Q.; Troye-Blomberg, M.; Akanmori, B.D.; Kurtzhals, J.A.L.; Dodoo, D.; Consolini, R.; Linde, A.; Wahlgren, M.; et al. (Scandinavian Journal of Immunology, 2005)
Children living in malaria-endemic regions have high incidence of Burkitt's lymphoma (BL), the aetiology of which involves Plasmodium falciparum malaria and Epstein-Barr virus (EBV) infections. Acute malarial infection impairs the EBV-specific immune responses with the consequent increase in the number of EBV-carrying B cells in the circulation. To further understand the potential influence of malarial infection on the EBV persistence in children living in malaria-endemic areas, we studied the occurrence and quantified cell-free EBV-DNA in plasma from 73 Ghanaian children with and without acute malarial infection. Viral DNA was detected in 40% of the samples (47% in the malaria-infected and 34% in the nonmalaria group) but was absent in plasma from Ghanaian adults and healthy Italian children. These findings provide evidence that viral reactivation is common among children living in malaria-endemic areas, and may contribute to the increased risk for endemic BL. The data also suggest that the epidemiology of EBV infection and persistence varies in different areas of the world. © 2005 Blackwell Publishing Ltd.